A meta-narrative analysis of smart tourism destinations: implications for tourism destination management. Issue 20 (18th October 2021) - Gelter, Jennie; Lexhagen, Maria; Fuchs, Matthias
ABSTRACT: The concept of smart tourism destinations has gained increased interest in tourism research. In this study, we show how previous research has shaped the current discourse on smart tourism destinations. By analysing meta-narratives, we outline how the use of language has influenced the research domain of smart tourism destinations. When the scope of a research field is broad and still unclear, a systematic meta-narrative analysis of the literature is recommended, to provide a holistic view and an understanding of how narratives unfold over time. Our findings highlight that there are certain words that dominate the contemporary discourse in this research field, presented as meta-narratives of smart tourism destinations. Our study shows how language plays an important role in providing frameworks for the research discourse and offers a legitimation of master ideas. By analysing the language used in published scientific texts for describing and defining smart tourism destinations, we identify the meta-narratives that build major language-based concepts and how these have formed the research field of smart tourism destinations.